Turning the spotlight: Hostile behavior in creative higher education and links to mental health in marginalized groups - Marina Fischer; Susanne Veit; Pichit Buspavanich; Gertraud Stadler (PLOS ONE, 2025)
Hostile, discriminatory, and violent behavior within the creative industries has attracted considerable public interest and existing inequalities have been discussed broadly. However, few empirical studies have examined experiences of hostile behavior in creative higher education and associated mental health outcomes of early career artists. To address this gap, we conducted a survey among individuals studying at higher education institutions for art and music (N = 611). In our analyses of different types of hostile behaviors and their associations with mental health and professional thriving, we focused on differences and similarities between marginalized and more privileged groups across multiple diversity domains. A substantial percentage of participants reported hostile behaviors in their creative academic environments. Individuals from marginalized groups reported more hostile behaviors, which partially explained their worse mental health and lower professional thriving. These findings indicate a clear need for the creative sector to implement strategies to create safer environments, particularly for early career artists from specific socio-demographic backgrounds. We conclude by suggesting strategies for prevention in this highly competitive industry.
Keywords: 330